A comparative study of Typhidot and Widal tests for the detection and diagnosis of Typhoid fever in patients. - Mensah, Lydia Kesewaa (2016)
A Thesis Submitted to the Department of Clinical Microbiology, Kwame Nkrumah University of Science and Technology in Partial Fulfillment of the Requirement for the Degree of Master of Philosophy (Clinical Microbiology).